Divergent Responses of Dominant Forest Tree Species to Manipulated Canopy and Understory N Additions in Terms of Foliage Stoichiometric, Photosynthetic, and Hydraulic Traits. Issue 10 (15th October 2021) - Zhang, Zhenzhen; Zhao, Ping; Ouyang, Lei; Zhao, Xiuhua; Zhu, Liwei; Ni, Guangyan
Abstract: Nitrogen (N) deposition effects on the stoichiometric balance and photosynthetic and hydraulic couplings in subtropical forests has drawn wide attentions. The previously adopted understory application of N fertilization is criticized because it might ignore foliar N retention for different species. This paper reports a fertilizing application from the canopy (CAN) and under the canopy (UAN) in a phosphorus (P) limited ecosystem. Foliage stoichiometric, photosynthetic, and hydraulic traits of six dominant species were measured and analyzed. Both treatments equally enhanced foliage N and N/P, but not foliage P, who was highly species‐specific depending on tree height, which implied enhanced P limitation. Decreased isotope abundance of 15 N (δ 15 N) that approaching to the level in the urea fertilizer under CAN suggested the existence of canopy retention of N. Besides, N response sensitivity of N, P and δ 15 N that positively related to tree height (H) under CAN indicated different exposure to the added N, which promoted stoichiometric imbalance among species. The photosynthetic traits represented by net photosynthesis ( A n ) increased under both treatments. A divergent foliar photosynthetic and hydraulic traits variation was identified by significant decreased stomatal conductance ( g s ) and A n / g s for CAN treatments, which induced the elevated isotope abundance of 13 C (δ 13 C). Correspondingly, foliage hydraulic traits that shifted to water use efficiency axis were identified only under CAN in principal component analysis. Overall, our results proved that the canopy absorption and species heterogeneity should be considered regarding foliar safety versus efficiency trade‐off in response to nitrogen additions in the future. Plain Language Summary: The nitrogen components released to the atmosphere due to human activities during the past centuries have been mostly transported to the forests via precipitation, which is officially called "wet nitrogen deposition." Just like chemical fertilization in the agriculture, these nitrogen components will not only influence the growth of these "giant crops, " but also alter their resistance capacity to harsh environment, such as drought, heat wave and so on. In this study, we simulated a "leaf fertilizer" experiments in a natural forest via many 30 m‐height towers. We checked the leaf performance via some scientific instruments and laboratory tests. We found that the fertilization will lead the plant nutritional imbalance and vulnerability increase, and the taller species will snatch much more resources to suppress shorter one. Besides, we also compared the leaf fertilization with the traditional soil fertilization, who was widely used to study the fertilization effects on these "giant crops." We found that the later did not bring about the plant performances above. Thus, scientists should be more cautious in the future, if they want to know what will happen to the forest under persistent wet nitrogen deposition. Key Points: Although stoichiometric balance was indeed shifted in the subtropical forest, the decoupling of plant photosynthesis and the hydraulic traits was not disturbed The upper canopy species experience stronger nutrient stoichiometric shifts than the lower‐canopy species The under the canopy application failed to detect the resources redistribution among different species and the strengthened decoupling relation between photosynthesis and hydraulic traits